Effect of chemotherapy/targeted therapy alone vs. chemotherapy/targeted therapy followed by radical surgical resection on survival and quality of life in patients with limited-metastatic adenocarcinoma of the stomach or esophagogastric junction: the IKF-575/RENAISSANCE phase III trial : [Meeting Abstract: 2024 ASCO Annual Meeting II] - Batran, Salah-Eddin al-; Lorenzen, Sylvie; Riera, Jorge; Caca, Karel; Müller, Christian; Stange, Daniel Eduard; Zander, Thomas; Bolling, Claus; Homann, Nils; Gaedcke, Jochen Werner Christian; Thuss-Patience, Peter C.; Michl, Patrick; et al. (Journal of clinical oncology, 2024)
LBA4001 - Background: The IKF-575 trial investigates the long-standing question about the role of surgical intervention in limited-metastatic gastric / esophagogastric junction cancer after systemic induction therapy. Methods: Previously untreated patients (pts) with limited metastatic disease (retroperitoneal lymph node (RPLN) metastases only or a maximum of one incurable organ site that is potentially resectable or locally controllable with or without retroperitoneal lymph nodes) received 4 cycles of FLOT, + trastuzumab if Her2+ or + nivolumab if PD-L1 positive. Pts without progression after 4 cycles were randomized to receive additional FLOT (Arm B) or radical complete surgical resection of primary and metastases followed by the same treatment (Arm A). It was planned to randomize 176 pts for which 271 pts had to enrolled. The primary endpoint was overall survival in the ITT population using Kaplan-Meier estimates. Recruitment was stopped after enrollment of 183 patients (141 patients randomized) with minimal impact on statistical power, due to a slow enrollment rate. Results: The ITT comprised 139 pts (A, 67; B, 72): 20% had RPLN metastases only, 58% organ metastases only, and 22% had both. Surgery in Arm A (ITT) was performed in 91% of pts and R0-resection rate (primary) was 82%. 30-d and 90-d mortalities in the surgery population were 3% and 8%. At least 4 additional cycles of post-op or post-randomization chemotherapy were achieved in 42% of pts in Arm A vs. 71% of pts in Arm B. The primary endpoint ovrall survival was not met due to increased early mortality in the surgery Arm leading to crossing survival curves with OS 25%- and 75%-Quantiles being 10 vs. 14 months and 65 vs. 41 months for Arms A vs. B, respectively. Pts with RPLN metastases only seemed to benefit most from the surgical approach (mOS, 30 vs. 17 months; 5y OS 38% vs. 19%; still having increased early mortality), while pts showing no response to chemo (mOS, 13 vs. 22 months) or pts with peritoneal disease (mOS, 12 vs. 19 months) derived a detrimental effect. Conclusions: The IKF-575/RENAISSANCE trial is negative but informs future research. Future protocols should focus on pts with RPLN only disease and exclude non-responding pts or those with peritoneal disease. There is a need for strategies against the early mortality caused by chemotherapy interruption. Clinical trial information: NCT02578368.
Gesehen am 10.03.2025